Esketamine for Unipolar Major Depression With Psychotic Features: A Retrospective Chart Review and Comparison With Nonpsychotic Depression. Issue 4 (21st July 2022) - Souza-Marques, Breno; Telles, Manuela; Leal, Gustavo C.; Faria-Guimarães, Daniela; Correia-Melo, Fernanda S.; Jesus-Nunes, Ana Paula; Vieira, Flávia; Souza, Lucca; Lins-Silva, Daniel; Mello, Rodrigo P.; Guerreiro-Costa, Lívia; Bandeira, Igor D.; et al.
Abstract: Purposes/Background: The aims of the study were to assess subanesthetic esketamine as an antidepressant for major depressive disorder with psychotic features (PMDD) and to compare posttreatment symptoms among those with PMDD to a sample of nonpsychotic depression (major depressive disorder [MDD]). Methods/Procedures: This study is a retrospective chart review of patients with major depression and current psychotic symptoms, treated with a single parenteral 0.5-mg/kg dose of esketamine. Depression symptoms were assessed at baseline and 24-hour posttreatment with the Montgomery-Åsberg Depression Rating Scale. Individuals with PMDD were matched in a 1:2 ratio to nonpsychotic MDD patients from a randomized, noninferiority clinical trial of esketamine. Findings/Results: A total of 15 individuals with PMDD were included, which had higher baseline depression scores (PMDD = 40.9, MDD = 33.6, P = 0.004). A statistically significant change in depressive symptoms was found for the PMDD sample (β = −16.20 [95% confidence interval, −23.30 to −9.10], P < 0.001), and no difference between PMDD and MDD groups was observed in the matched-sample analysis (β = −2.2 [95% confidence interval, −9.32 to 4.58], P = 0.537). Treatment-induced dissociative symptoms were present for both groups, self-contained to within 2 hours after treatment, and no exacerbation of psychotic symptoms was found in clinical assessments. Implications/Conclusions: Results suggest a single 0.5-mg/kg dose of esketamine may benefit individuals with PMDD, and the symptom reduction may be comparable with esketamine's effects for MDD. Furthermore, esketamine may induce an antidepressant response in those with PMDD without complication of psychotic symptoms. Future research with controlled designs is warranted.